Nuclear logics : contrasting paths in East Asia and the Middle East - Solingen, Etel, 1952- (Princeton studies in international history and politics., 2007)
Nuclear Logics examines why some states seek nuclear weapons while others renounce them. Looking closely at nine cases in East Asia and the Middle East, Etel Solingen finds two distinct regional patterns. In East Asia, the norm since the late 1960s has been to forswear nuclear weapons, and North Korea, which makes no secret of its nuclear ambitions, is the anomaly. In the Middle East the opposite is the case, with Iran, Iraq, Israel, and Libya suspected of pursuing nuclear-weapons capabilities, with Egypt as the anomaly in recent decades. Identifying the domestic conditions underlying these divergent paths, Solingen argues that there are clear differences between states whose leaders advocate integration in the global economy and those that reject it. --From publisher's description.